THE ANTI-APOPTOTIC POTENTIAL OF Paederia foetida L. LEAF EXTRACT THROUGH THE DOWNREGULATION OF CASPASE-3 EXPRESSION IN AN ESCHERICHIA COLI-INDUCED SEPSIS MICE MODEL - Savitri, Lisa; Krissanjaya, Rochmad; Juwita, Syntia Tanu; Sukmawati, Datin An Nisa; Probosiwi, Neni; Laili, Nur Fahma; Ilmi, Tsamrotul; Prasetyawan, Fendy (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Sepsis is a life-threatening condition characterized by an abnormal immune response to infection, leading to high mortality rates in intensive care units (ICUs) worldwide. Caspase-3, a crucial enzyme in the apoptosis pathway, plays a significant role in sep-sis-related cellular damage. This study investigates the anti-apoptotic potential of Paederia foetida L. leaf extract by examining its effect on Caspase-3 expression in an Escherichia coli-induced sepsis mice model. Male Balb/c mice were divided into six groups, including positive control, negative control, and treatment groups receiving varying doses of the extract (100 mg/kgBW, 300 mg/kgBW, and 500 mg/kgBW). Caspase-3 expression in the spleen was measured after 24 hours of treatment. The results demonstrated a significant reduction in Caspase-3 expression, particularly in the group treated with 500 mg/kgBW of the extract, indicating its anti-apoptotic effect. These findings suggest that P. foetida leaf extract may serve as a potential therapeutic agent for reducing cell apoptosis in sepsis, warranting further investigation into its mechanisms and clinical pharmacological field.